Efficacy of different concentrations of Rotstop® and RotstopS and imperfect cover of RotstopS against Heterobasidion spp. infections on Norway spruce stumps - Sidorov, Evgeny (SLU/Southern Swedish Forest Research Centre, 2005)
The effectiveness of treatment with two Phlebiopsis gigantea based preparations (Rotstop® and RotstopS) in different concentrations against the root and butt rot causing fungus Heterobasidion annosum s.l. on Norway spruce (Picea abies) thinning stumps in southern Sweden was compared. The trees were cut on three sites during the summer 2004 and 285 stumps were treated manually with 100% cover with two different amounts of spores in solution corresponding to approximately 5×106 spores/l and 10×106 spores/l. 31 stumps received mechanical part cover with the highest spore concentrations of Phlebiopsis gigantea, i.e. approximately 20×106 spores/l. Mechanical treatment was assessed for satisfactory treatment effect. Three months later, samples were collected and analyzed.